An anatomy of trade in medieval writing : value, consent, and community - Farber, Lianna (Cornell University Press, 2006)
"Economics, in our modern sense of the term, was not a discipline in the Middle Ages, although the history of economic thought is often written as though it were. Lianna Farber restores the core economic concept of trade to its medieval contexts, showing that it contains three component parts: value, consent, and community. Medieval writing about trade not only relies on these elements, it presents them as unproblematic."